Banking mediation in business registration: advantages and limitations ("Journal "U". Economy. Management. Finance.", 2025)
The article analyses the mechanism of banking mediation in business registration in the Russian Federation. It demonstrates how banks simplify the registration procedure through agreements with the Federal Tax Service (FTS). The study identifies key limitations of this approach, highlights persistent challenges in the registration process, and outlines the general trend towards simplifying administrative procedures in the entrepreneurial sphere.
Keywords: bank; services; state registration; tax authority; business entity